STEROIDAL SAPOGENINS 162 KAPPOGENIN AND FURCOGENIN - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
Furcogenin has been found to be a mixture of smilagenin and hecogenin. Kappogenin has been found to be a mixture of nologenin and pseudodiosgenin.
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS. 162., KAPPOGENIN, FURCOGENIN; QUIMICA; BIOQUIMICA; BIOQUIMICA FISICA